2018
DOI: 10.1016/j.ebiom.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib for Epidermal Growth Factor Receptor Activated Osteoarthritis Subpopulation Treatment

Abstract: Osteoarthritis (OA) is a leading cause of physical disability among aging populations, with no available drugs able to efficiently restore the balance between cartilage matrix synthesis and degradation. Also, OA has not been accurately classified into subpopulations, hindering the development toward personalized precision medicine.In the present study, we identified a subpopulation of OA patients displaying high activation level of epidermal growth factor receptor (EGFR). With Col2a1-creERT2; Egfrf/f mice, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Since early studies have demonstrated that OA initiation in dog and cyclic impact loading on cartilage explants significantly elevate Mig‐6 mRNA level in chondrocytes, we reason that the downregulation of EGFR activity during early OA is potentially due to the abnormal loading‐induced Mig6 action and therefore could occur without changes in ligand availability. At the late stage of OA, it was reported that human OA samples (between 3 and 4 in the Kellgren and Lawrence grading system), as well as rat samples after OA surgery, contain significantly more activated EGFR than controls. These temporal changes of EGF‐like ligands and EGFR activity during OA progression strongly implicate that EGFR signaling is involved in OA pathology but possibly in a stage‐dependent manner.…”
Section: The Importance Of Egfr Signaling In Osteoarthritis (Oa)mentioning
confidence: 99%
“…Since early studies have demonstrated that OA initiation in dog and cyclic impact loading on cartilage explants significantly elevate Mig‐6 mRNA level in chondrocytes, we reason that the downregulation of EGFR activity during early OA is potentially due to the abnormal loading‐induced Mig6 action and therefore could occur without changes in ligand availability. At the late stage of OA, it was reported that human OA samples (between 3 and 4 in the Kellgren and Lawrence grading system), as well as rat samples after OA surgery, contain significantly more activated EGFR than controls. These temporal changes of EGF‐like ligands and EGFR activity during OA progression strongly implicate that EGFR signaling is involved in OA pathology but possibly in a stage‐dependent manner.…”
Section: The Importance Of Egfr Signaling In Osteoarthritis (Oa)mentioning
confidence: 99%
“…Ageing, obesity, gender, increased biomechanical loading of joints, and genetics or low-grade systemic inflammation have been known as risk factors for OA [ 9 , 10 ]. Although the mechanistic details of OA pathogenesis remain to be elucidated, the cartilage degradation and inflammation is the most predominant pathological feature that inevitably leads to joint dysfunction [ 11 , 12 ]. The articular cartilage is composed of water and extracellular matrix (ECM), which mainly composed of Type II collagen, aggrecan, proteoglycans and other collagen subtypes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The articular cartilage is composed of water and extracellular matrix (ECM), which mainly composed of Type II collagen, aggrecan, proteoglycans and other collagen subtypes [ 10 ]. Thus, the cartilage homeostasis is maintained by the balance between ECM synthesis and degradation [ 12 ]. Disturbances of this balance are one of the main characteristics of OA cartilage, and the restoration of balance is the key factor for cartilage regeneration in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Mig-6 overexpression has been demonstrated in OA cartilage in dogs (38), suggesting that the same could occur in human OA. More generally, the EGFR pathway, through which Mig-6 primarily acts, has been shown to be deregulated in human OA in several studies (21,34,72).Thus, the current study is highly relevant to the pathogenesis of human OA.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the role of Mig-6 in human OA will require further studies. While there is plenty of evidence for crucial roles of the EGFR pathway in human OA, and Mig-6 is a crucial regulator of this pathway, more direct analyses of this role in human cartilage is required (21,71,72).…”
Section: Discussionmentioning
confidence: 99%